Tinjauan Pendidikan Dalam Perspektif Islam - Ahmad Djuaeni (STAI Siliwangi Bandung, 2016)
Islamic education is a conscious effort to form bio-psycho socio-spiritual of human being through guidance, instruction and training for the sake of its role in the future for being the caliph fil 'ard. In the implementation of all must be based on the Quran and al-Hadith, if both are not available, the use of ijtihad is allowed. Criteria to be perfect man, should has characteristics of Muhammad; shidiq, trustworthy, and fathonah, no exception learners live in a conducive environment to both formal, informal and non-formals.